2007
DOI: 10.1021/om061071v
|View full text |Cite
|
Sign up to set email alerts
|

Palladacycle Chemistry on the Edge of Naphthalene and Triphenylene:  Alkyne Cycloadditions and Autocatalytic Coupling

Abstract: The four-membered palladacycle Pd(PEt3)2(1,8-naphthalenediyl) (3) and the five-membered palladacycle Pd(PEt3)2(1,12-triphenylenediyl) (4) were prepared from Pd(PEt3)2Cl2 and the appropriate dilithio reagent. Both palladacycles are thermally unstable, decomposing autocatalytically at 100 °C to palladium black, Pd(PEt3)3, and perylene (for 3) or dinaphtho[def,pqr]tetraphenylene (for 4). In the presence of PhCCPh, the decomposition is slowed and the cycloaddition products 1,2-diphenylacenapthylene (for 3) and 4,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 55 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…Perhaps other effects may also contribute to the elimination in para ‐xylene. For example, wall effects, autocatalysis by colloidal Pd 0 , or the participation of other molecules could play a role. The formation of the isomeric elimination products 4 b and 4 c (cf.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps other effects may also contribute to the elimination in para ‐xylene. For example, wall effects, autocatalysis by colloidal Pd 0 , or the participation of other molecules could play a role. The formation of the isomeric elimination products 4 b and 4 c (cf.…”
Section: Resultsmentioning
confidence: 99%
“…Previously an incorporation of ap hosphorus(V) center into the {CNN} coordination core of carbaporphyrinoid has been reported for N-fused dihydrotelluraporphyrin. [27][28][29] Them ethoxide ligands at the phosphorus(V) center are readily exchangeable for hydroxides during chromatography on basic alumina or if traces of water are present in asolvent as documented by 1 HNMR spectroscopy ( Figure S25). [24,25] Nevertheless,t he binding component where the C(4) and C(5) carbon atoms of phenanthrene (where the numbers refer to "free" phenanthrene) are simultaneously bound has been recognized in silylated phenanthrenes [26] and metalated triphenylene derivatives.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…For instance, the palladacycle 27 was isolated from the reaction of [PdCl 2 (PEt 3 ) 2 ] with the TMEDA (Me 2 NCH 2 CH 2 NMe 2 ) adducts of 1,8-dilithionaphthalenediyl (Scheme 19). [26] Double transmetalation reactions are not limited the use of organolithium reagents, as shown by Vicente et al [27] They reported the synthesis of several four-membered palladacycles by reaction of dimeric bis-ylide silver(I) complexes with [PdCl 2 (NCPh) 2 ] (Scheme 20). Depending on the molar ratio Ag/ Pd used, mononuclear (28 a and 28 b) or dinuclear metallacycles (29 a and 29 b) were obtained.…”
Section: Synthesis Involving Transmetalation Reactionsmentioning
confidence: 99%